Power relation of the 212 Islamic Group and the government in the 2019 presidential election - Moch. Mubarok Muharam; Kacung Marijan; Airlangga Pribadi Kusman (Masyarakat, Kebudayaan dan Politik, 2021)
The 212 Islamic Group was in opposition with the government of Joko Widodo (Jokowi) in the 2019 presidential election. This group made militant resistance against Jokowi in the presidential election. This resistance influenced the presidential election contestation became more dynamic and fierce. The fierce contestation had divided the community into two camps, namely the pros and cons of Jokowi. This study explored and analyzed the resistance of the 212 Islamic Group against the government in the 2019 presidential election. This study was a qualitative study, interviewing 12 informants, consisting of the 212 Islamic Groups, Moderate Islamic Groups, Indonesian Ulema Council, online media, and academics. This study showed that The 212 Islamic Group can offset the government’s political influence so that the presidential election becomes more dynamic and balanced. However, the resistance of this group can be substantial (prominent) because of the narration about the rise of Islam and their ability to ideologize mosques and social media. This paper concluded that there was a resistance of the 212 Islamic Group to the country because Jokowi was considered secular and detrimental to Islam in politics and law, such as disbanding Hizbut Tahrir Indonesia (HTI).